Matter-wave interferometry for quantum sensing - Pessoa Junior, Claudio Alves (2024)
This dissertation reports on advancements in the construction of a quantum sensor for gravimetry based on matter interferometry. Ultra-cold strontium atoms (in the order of 1 μK) within a ring cavity in the bad cavity regime constitute the experimental setup and two distinct approaches were adopted for the comprehension of the systems operation. The first involved simulations of Ramsey-Bordé pulse sequence, specifically the π/2-π-π/2-spin echo sequence using the 689 nm transition of strontium. The sequence is commonly employed in matter interferometers and the simulations provided insights for future measurements. The expected precision of our system is within Δg/g < 10-8, showcasing its potential accuracy. The second approach focused on monitoring Bloch oscillations resulting from the interaction between atoms and cavity light, which induces a frequency proportional to the external force, in our case, gravity. Efforts were made during the experiment towards confirming the systems regime, leading to a significant observation of nonlinear Normal-mode splitting due to high saturation in the strong coupling regime, exhibiting a bi-stable behaviour.